Realizing the circular economy for sanitation: assessing enabling conditions and barriers to the commercialization of human excreta derived fertilizer in Haiti and Kenya - Moya, Berta; Sakrabani, Ruben; Parker, Alison (MDPI, 2019)
Efficient fecal sludge management solutions are especially challenging in densely populated urban informal settlements, where space is limited and land tenure uncertain. One solution is to collect and treat human excreta to produce soil conditioners for use in agriculture, through container-based sanitation, thus realizing the circular economy for sanitation. This study focused on container-based sanitation ventures that produce and sell fertilizers from human excreta. Stakeholder interviews showed that challenges faced by these ventures were similar: unclear regulations on the use of fertilizers derived from source-separated excreta, undeveloped markets for organic fertilizers, difficulties in securing secondary sources of organic matter for composting as well as complex transport and distribution logistics. The findings of this study emphasized the need for clear policies with respect to human excreta derived fertilizer, as well as institutional involvement in order to incentivize the sale and use of human excreta derived fertilizer locally to ensure that sustainable and safely managed sanitation systems are available in urban areas.
Keywords: fertilizer; sanitation; fecal sludge; business models; certifications